Kedudukan Hukum Lembaga Perkreditan Desa (LPD) Dalam Sistem Lembaga Keuangan Mikro - Kadek Bagas Piadnyan; I Nyoman Putu Budiartha; Desak Gede Dwi Arini (Jurnal Analogi Hukum, 2020)
Abstract—Village Credit Institutions (LPD) as an institution established specifically for the sake of the welfare of the Pakraman Village community, Village Credit Institutions do not serve outside of the Pakraman Village area where the Village Credit Institution operates. The establishment of Village Credit Institutions (LPDs) began to be carried out and the existence of LPDs was regulated under Regional Regulation (PERDA) namely Bali Provincial Regulation Number 8 of 2002 concerning Village Credit Institutions (LPD), which have now been changed to Bali Provincial Regulation Number 3 of 2017. The Regional Regulation regulates the conditions for the Establishment of Village Credit Institutions (LPD). The problem statement is: 1) What is the legal position of the Village Credit Institution (LPD) in the Micro Finance Institution system? 2) What is the role of Village Credit Institutions (LPDs) in the Micro Finance Institution system? The research method used is normative legal research. The source of legal material that will be used is the research source of primary, secondary and tertiary materials. The techniques for collecting primary and secondary legal materials were collected based on the topic of the program which had been formulated based on the snowball system and disclassified according to sources and hierarchies to be presented comprehensively. Analysis of legal materials with legal interpretation and presented in the form of analysis descriptions. The legal position of the Village Credit Institution based on the customary law community in Bali in the Micro Kauangan Institution system according to Law Number 10 of 1998 concerning Banking cannot be equated. The Village Credit Institution has a very strategic role because so far it has been serving small micro enterprises (MSEs) and rural communities in Bali through financial services that are carried out in accordance with customer needs, personal approaches, and proximity to customers.